Usage of scientific-methodological materials in the educational process of the higher educational institute - Halahdina, A. A.; Herasym, L. M. (Journal of Education, Health and Sport, 2019)
The article highlights the issue of the functional purpose of scientific-methodical providing of the learning process of the institution of higher education, modern requirements to it, teaching complex of the discipline and its components.